Desarrollando habilidades financieras en estudiantes vulnerables de Soacha: Estrategias académicas efectivas - Villamil Escobar, Leslie Carolina (Universidad Antonio Nariño, 2023)
The objective of this research was to design, implement and evaluate effective pedagogical strategies for the development of financial skills in vulnerable students in Comuna IV of Soacha. A mixed approach was used that combined the review of school records, consultation with teachers and school administrators, and the application of student surveys.